Democratic adult education as a research problem in the context of post-democracy - Lima, Licínio (Adult Education Discourses, 2023)
Adult learning and education (ALE) policies are studied in this essay in relation to various conceptions of democracy, and of post-democracy. The author observes that the dominant political discourses, notably in the European Union, have been influenced by technocratic conceptions of ALE. In this context, and invoking the imperatives of the knowledge society, ALE for cognitive democracy and for participatory forms of deliberative democracy tends to be diminished by elitist theories. This results in the subordination of ALE to formal democracy and proceduralism, as well as to hetero government carried out by specialists. The post-democratic dimensions in ALE policies have weakened the potential for promoting an educated democracy and the development of a knowledge democracy capable of recognising different educational epistemologies and various forms of knowledge. Understanding the processes that have led to an erosion of democracy in ALE public policies requires the study of the impacts produced by new meritocratic ideologies and expertocracy, induced by discourses around the global race for talent. It is concluded that more than a century of democratic educational thinking, of various shades, have been overtaken by the impacts of new managerialism on education, under the rigours of meritocracy, efficiency, and competitive performativity. These and other elements of the global education reform constitute research problems confronting educational communities and academic researchers. They are required to understand the politicityin their research agendas and to democratise it, seeking to strengthen their relative autonomy for critical inquiry.